The impact of Ramadan fasting on hydration status of type 2 diabetics in Kubang Kerian, Kelantan - N. Azwany; Aziz A. I.; W. Mohammad (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2004)
Ramadan fasting involves abstaining from all form of oral intake including fluids from the beginning of dawn till sunset. This stucfy aimed to study the impact of Ramadan fasting on the hydration status of type 2 diabetes patients. A total of 43 Muslims type 2 diabetes with no renal, cardiovascular and acute complications were studied. Urine osmolality and blood urea samples were collected on four consecutive visits, four weeks and one week before Ramadan, fourth week of Ramadan and four weeks after Ramadan. Significant increased in urine osmolality as noted on fourth week of Ramadan (p<0.001) but still in the normal acceptable range of hydration. Blood urea showed a non-significant increased on fourth week of Ramadan (p=0.186). These findings suggest that water restriction during fasting Ramadan was not sufficient to cause dehydration in uncomplicated type 2 diabetes patients.